2019
DOI: 10.3906/tar-1803-109
|View full text |Cite
|
Sign up to set email alerts
|

Tree vigor, yield, fruit quality, and antioxidant capacity of apple (Malus × domestica Borkh.) influenced by different fertilization regimes: preliminary results

Abstract: Introduction Apples are the most important and most popular fruit crop in temperate climate zones, and their production is increasing. The apple is a convenient fruit available in retail throughout the world all year as a result of its high storability. Its beautiful appearance, crispy flesh, pleasant flavor, and sweetness attract consumers and fetch a high price (Asif Ali et al., 2004). Appearance, fruit size, uniformity, color, and freshness, as well as nonvisual attributes such as taste, aroma, flavor, firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…For other fruits, which are sweeter than tart cherries, the sweetness/sourness TS/TA ratio is higher. For Idared apples the TS/TA ratio was 19.7–28.5 [ 23 ], for apricots 8.4–9.2 [ 24 ], but for pomegranates and cornelian cherry it was 2.3–7.0 [ 14 , 25 ]. This acceptability index in sweet cherries can be above the value of 25 [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…For other fruits, which are sweeter than tart cherries, the sweetness/sourness TS/TA ratio is higher. For Idared apples the TS/TA ratio was 19.7–28.5 [ 23 ], for apricots 8.4–9.2 [ 24 ], but for pomegranates and cornelian cherry it was 2.3–7.0 [ 14 , 25 ]. This acceptability index in sweet cherries can be above the value of 25 [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fruit weight as a cultivar-specific property can be improved by cultural practices such as fertilisation, irrigation, pruning, thinning, spraying with foliar nutrients and hormones etc. (Greenhalgh et al, 1977;Milošević et al, 2014Milošević et al, , 2019, crop load, rootstock (Milošević et al, 2018) and choice of environmental conditions suitable for apple growing. In the present study, significantly higher fruit weight was found in 'Hapke' on M.9 T337 in comparison with M.26 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Fermentation at lower temperatures resulted in longer fermentation times, 24-29 days when using M02 yeast and 39 and 56 days for the spontaneously fermented ciders (Table 1). In apples, the content of nitrogen is affected by cultivar, soil, fertilization, climatic conditions and the age of the apple trees (Milosevic, Milosevic & Mladenovic, 2019;Planchon, Lateur, Dupont & Lognay, 2004). To prevent fermentation from stopping, a sufficiently high amount of nitrogen is necessary (Lea, 2015) .…”
Section: Resultsmentioning
confidence: 99%